The correlation study between the length and angle of ascending aortic and the incidence risk of acute type A aortic dissection - Li, Bowen; Meng, Xiangbin; Fu, Chao; Yang, Zhihao; Zhao, Xin (Frontiers in Cardiovascular Medicine, 2024)
Objective This study utilized computed tomography angiography (CTA) to assess the risk of acute type A aortic dissection (ATAAD) by analyzing the imaging morphology indicators of the ascending aorta, along with the relevant risk factors associated with aortic dissection. Methods The study utilized a retrospective observational research design. The population consisted of 172 patients who received treatment in the Department of Cardiothoracic Surgery at Qilu Hospital, Shandong University, from January 2018 to December 2022. The patients were divided into two groups: the ATAAD group (n = 97) and the thoracic aortic aneurysm group (TAA, n = 75). Demographic data and ascending aorta CTA measurements were collected from all patients. Single factor and multivariate logistic regression were employed to analyze the statistical differences in clinical data and ascending aorta CTA imaging morphology indicators between the two groups. Results The variables were included in logistic multivariate analysis for further screening, indicating that the length of the ascending aorta (LAA) before ATAAD (OR = 3.365; 95% CI :1.742–6.500, P<0.001), ascending arch angle (asc-arch angle, OR = 0.902; 95% CI: 0.816–0.996, P = 0.042) and the maximum aortic diameter (MAD) before ATAAD, (OR = 0.614; 95% CI: 0.507–0.743, P<0.001) showed statistically significant differences. Conclusions This study suggests that increased LAA and MAD, as well as a smaller asc-arch angle may be high-risk factors for the onset of ATAAD.